2008
DOI: 10.1111/j.1471-4159.2008.05522.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of neural progenitor cell development in the nervous system

Abstract: The mammalian telencephalon, which comprises the cerebral cortex, olfactory bulb, hippocampus, basal ganglia, and amygdala, is the most complex and intricate region of the CNS. It is the seat of all higher brain functions including the storage and retrieval of memories, the integration and processing of sensory and motor information, and the regulation of emotion and drive states. In higher mammals such as humans, the telencephalon also governs our creative impulses, ability to make rational decisions, and pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
100
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(103 citation statements)
references
References 121 publications
(137 reference statements)
0
100
0
3
Order By: Relevance
“…As a conservative neuronal developmental signaling pathway, Notch plays a critical role in neural stem cell maintenance (Corbin et al, 2008). With the theory that tumors originate from stem cells, the Notch signaling pathway has been recently studied in the aspect of its relevance in glioma formation.…”
Section: Notch Signaling Pathways and Potential Therapeutic Approachesmentioning
confidence: 99%
“…As a conservative neuronal developmental signaling pathway, Notch plays a critical role in neural stem cell maintenance (Corbin et al, 2008). With the theory that tumors originate from stem cells, the Notch signaling pathway has been recently studied in the aspect of its relevance in glioma formation.…”
Section: Notch Signaling Pathways and Potential Therapeutic Approachesmentioning
confidence: 99%
“…Notch signaling is thought to maintain ''stemness'' and to prevent exit from the cell cycle and maturation (Basak and Taylor, 2009). However, its role in adult neurogenesis remains unclear, primarily because Notch plays so many other roles in maturation, neuroplasticity, and survival (Carlson and Conboy, 2007;Corbin et al, 2008 (Backman et al, 2001;Kwon et al, 2001;Groszer et al, 2001). Conditional knockout of Pten in neural stem cells revealed that Pten is indispensable for proper control of neural stem cell proliferation and self-renewal in the developing brain (Groszer et al, 2001).…”
Section: Developmental Dynamicsmentioning
confidence: 99%
“…The Notch signalling pathway controls neural differentiation and is known to maintain NSC character and to inhibit neurogenesis. The Notch-Hes pathway is necessary for self-renewing cell division and thus, maintenance of the neural precursor population [10][11][12][13] . However, the significance of the regulation of c-Jun, Notch and other substrates by SCF(Fbw7) during neurogenesis has remained unclear to date.…”
Section: Introductionmentioning
confidence: 99%